Post-Secular Mirasism and Reforming Islam in Russia: From Euro-Islam to Confessional Scholarship - Garaev, Danis (Islam and Christian-Muslim relations, 2023)
This article offers a view of the process of the formation of post-Soviet Islam in Russia as a result of the post-secular interaction between academic and religious areas – the boundaries between which are shown to be significantly blurred. It argues that, in the study of post-Soviet Islam, insufficient attention has been paid to the complex interactions between Islam and the Russian academic field. The article aims to fill this gap by providing examples of how, on the one hand, secular scholars become Muslim actors – bringing their secular, most often Soviet intellectual baggage to the Muslim sphere – and, on the other, how members of the Muslim clergy seek to influence the Russian academic community by claiming a role in the production of academic knowledge about Islam and Muslims as equal actors. Despite the post-secular nature of this interaction, it is the secular academic side that dominates.